The Effect of BI Rate and Money Supply and Exchange Rate on Inflation in Indonesia - Saputro, Hendra Rudianto; Busari, Arfiah; Kurniawan A, Erwin; Zulfikar, Akbar Lufi (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
In increasingly complex and competitive organizational dynamics, leadership style becomes a crucial factor in determining the success of an organization. This has resulted in leaders adopting a more proactive approach in improving the quality of employee work. Therefore, an analysis of transformational leadership style is needed by leaders of health service providers to improve the quality of employee work. The aim of this research is to determine the relationship between transformational leadership style and the quality of employee work at the Kubur Jawa Community Health Center, Hulu Sungai Tengah Regency. The research is quantitative research with analytical survey research methods with a cross-sectional approach. This research was conducted from January 2024 to June 2024. The population of this research was all employees at the Kubur Jawa Community Health Center. The research sample was taken by purposive sampling and consisted of 46 employees. The research results show that there is a relationship between inspirational motivation (p-value=0.000), intellectual stimulation (p-value=0.000), individual consideration (p-value=0.027), and ideal influence (p-value=0.005) with quality employee work. there is a relationship between transformational leadership style and inspirational motivation, intellectual stimulation, individual consideration, and ideal influence with the quality of employee work at the Kubur Jawa Community Health Center